The Influence of the Value Changes on the Perception of Costume Colour (Journal of Fiber Bioengineering and Informatics, 2018)
The purpose of this study was to investigate the relationship between perceptual attributes of costume colour and the colour value changes. In this study, “gorgeous” and “plain” as words for description of human colour emotion were used, and costume picture samples and colour piece samples of same colours with 40 hues and 9 levels of values were evaluated on emotion variables by 32 subjects in the behavioural trials. The results showed that the colours of medium values have the most gorgeous emotion, and presented sensitivity to subjects during the evaluation of “gorgeousness”, the RT (response time) of costume is less than the RT of colour pieces, it is easier to make judgment on colour emotion in costume, while the lower-value-colour and the higher-value-colour reduce the effect on “gorgeous” emotion.